Pressure-driven electronegativity inversion in alkali liquids - Chenxu Han; Hongxiang Zong; Xiangdong Ding; Jun Sun; Graeme J. Ackland (Proceedings of the National Academy of Sciences, 2025)
Liquid–liquid phase transitions (LLPTs) are typically characterized as two-state systems, where transitions occur between two distinct liquid phases driven by local structural rearrangements. In this study, we observed a continuous LLPT with an inversion of electronegativity in a K–Rb binary alloy. This uniquely exhibits a three-state system behavior. The transition, induced by pressure-driven reordering of electronic orbital energies, progresses through a sequence from s -metal to electride to d -metal, accompanied by a valence reversal: Potassium transitions from a negative to a positive valence, while rubidium undergoes the opposite shift. This process is marked by two successive anomalies in the alloy’s optical, thermodynamic, and dynamic properties over a broad pressure range. The observation of similar LLPT phenomena in other alkali and alkaline earth metal liquids suggests that this three-state system mechanism may provide broader insights into the nature of continuous phase transitions.